Predicting low-impedance interfaces for solid-state batteries. Issue 3 (June 2022) - Swift, Michael W.; Jagad, Harsh; Park, Jiyun; Qie, Yu; Wu, Yuqin; Qi, Yue
Graphical abstract: Highlights: DFT-informed theory predicts inner potential maps in solid-state batteries. Potential drops lead to "intrinsic" interfacial impedance. Computed dictionary of potential maps for 48 distinct solid-state batteries. Identified cathode/solid-electrolyte interfaces with low intrinsic impedance. Model bridges materials innovation with device performance. Abstract: All-solid-state batteries are an exciting technology for increased safety and energy density compared to traditional lithium-ion cells. Recently, we developed a theory of mapping inner potentials and thermodynamic driving forces specific to the solid-state batteries, allowing prediction of the "intrinsic" interfacial lithium barriers. This potential mapping methodology, based purely on calculated bulk and surface properties, enables fast screening of a variety of advanced solid electrolyte materials as well as a selection of cutting-edge high-voltage cathode materials, predicting properties of 48 distinct battery configurations. A number of cathode/electrolyte pairs are identified which have low "intrinsic" barriers to both the charge and discharge process at all states of charge, suggesting that they will most benefit from engineering efforts to reduce extrinsic interfacial impedance. These predictions agree well with available experimental measurements, which form only a subset of the predicted interfaces. Thus, this interface potential model will accelerate the design process from emerging materials to all-solid-state battery devices.